Best of the best award at MTE 2013 - Noor Syahidah, Sabran (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) took part in an exhibition and competition in the Malaysia Technology Expo (MTE) 2013 held at the Putra World Trade Centre, Kuala Lumpur on February 21-23, 2013.